RANCANG BANGUN MODUL PRAKTIKUM SISTEM EMBEDDED BERBASIS RASPBERRY PI (PENGONTROLAN DASAR LED, LED DOT-MATRIX, DAN SEVEN SEGMENT DISPLAY) - Muhammad Abdul Hadi; Pratolo Rahardjo; I Putu Elba Duta Nugraha (Program Studi Teknik Elektro UNUD, 2021)
Embedded system is microprocessor-based systems that are used to perform certainfunctions. Embedded systems learning is very much needed, especially for students ofElectrical Engineering, Faculty of Engineering, Udayana University. This is evidenced by theexistence of a new course, namely the Embedded + Lab System. To support the convenienceof practicum in the laboratory, in this study, an Embedded+Lab System practical guide will bedesigned and built by utilizing the Single Board Microcomputer Raspberry Pi. It is hoped thatthis Embedded+Lab System practical guide will be useful for Electrical Engineering students,Faculty of Engineering, Udayana University. This research carried out several basic designsthat will be used in the Embedded System module 1 practical experiment, namely the design ofa Light Emitting Diode (LED) control, LED DOT-Matrix, and seven segment display. The designof each control system will generally be divided into two parts, namely hardware design andsoftware design. The results of this study are a box 1 system embedded practical module andpractical guides, as well as the design of each control system, all of which work well.